(untitled) (PANGEEA, 2025)
The growth of the global population and the implementation of extensive urban development programs are responsible for the generation of millions of tons of construction, renovation and demolition waste (CR&DW). While wood and metal are typically recycled, concrete, bricks, and mortar are typically disposed of in landfills. The primary environmental concerns associated with CR&DW in landfills pertain to leachate, H2S gas emissions, and the presence of heavy metals, including iron (Fe), manganese (Mn), zinc (Zn), copper (Cu), lead (Pb), and cadmium (Cd). These ions contribute to long-term contamination of the environment. In light of these considerations, the present study investigated the potential of plaster, concrete, drywall, autoclaved aerated concrete and brick for the removal of Fe, Mn and Zn ions from AMD. The findings indicated that a solid/liquid ratio of 5/50 (g/mL) of concrete was sufficient to reduce the concentration of Fe, Mn and Zn below the limits set by Romanian legislation after 60 minutes.